Nutritional quality of vegetables from Malaysian urban community farming - Daud, Mohd Nazrul Hisham; Jabit, Mohd Lip; Ramli, Norhasni; Ghazali, Nur Syafini; Cho, Joanna Lee Ying; Omar, Azirah (Universiti Teknologi MARA (UiTM), 2024)
Urban community farming has garnered interest in Malaysia due to rising household expenditures and government support through various policies and initiatives. This study evaluates the nutritional quality of nine common vegetable varieties from seven established urban community farms in Malaysia to enhance community engagement. The nutritional quality evaluation focused on sugar content, gross energy, vitamin A, vitamin C and twelve types of minerals. The analysis was conducted using specialized instruments, including High Performance Liquid Chromatography (HPLC), bomb calorimeter, and Inductively Coupled Plasma - Optical Emission Spectrometry (ICP-OES). The results indicated that all the cultivated vegetables contain at least two types of common sugars, with three of them containing all the targeted sugars. The gross energy of the cultivated vegetables, typically associated with sugars, ranges from 2900 to 3800 joules/g, with okra from Seksyen 4, Bangi exhibiting the highest value. Certain vegetables contain vitamins, with pak choy demonstrating the highest levels of vitamin A and sawi exhibiting the highest levels of vitamin C, respectively. Regarding mineral content, all vegetables contain twelve minerals, with spinach displaying the highest variety, including boron (B), potassium (K), magnesium (Mg), and phosphorus (P). The findings demonstrated that the urban farming community can produce nutritious vegetables to meet daily consumption needs and additionally decrease community expenses.